Metformin Reduces the Risk of Diverticula of Intestine in Taiwanese Patients with Type 2 Diabetes Mellitus - Tseng, Chin-Hsiao (Frontiers in Pharmacology, 2021)
Aim: To investigate the risk of diverticula of intestine associated with metformin use. Methods: This retrospective cohort study used the Taiwan’s National Health Insurance database to enroll 307,548 ever users and 18,839 never users of metformin. The patients were followed up starting on January 1, 2006 and ending on a date up to December 31, 2011. To address confounding by indication, hazard ratios were derived from Cox regression based on the inverse probability of treatment weighting using propensity score. Results: During follow-up, newly diagnosed cases of diverticula were identified in 1828 ever users (incidence rate: 125.59 per 100,000 person-years) and 223 never users (incidence rate: 268.17 per 100,000 person-years). Ever users had an approximately 54% lower risk, as shown by the overall hazard ratio of 0.464 (95% confidence interval 0.404-0.534). While patients categorized in each tertile of cumulative duration of metformin therapy were compared to never users, a dose-response pattern was observed with hazard ratios of 0.847 (0.730-0.983), 0.455 (0.391-0.531) and 0.216 (0.183-0.255) for the first (< 27.37 months), second (27.37-59.70 months) and third (> 59.70 months) tertiles, respectively. The findings were similar when the diagnosis of diverticula was restricted to the small intestine or to the colon. Subgroup analyses suggested that the lower risk of diverticula of intestine associated with metformin use was significant in all age groups of <50, 50-64 and ≥ 65 years, but the magnitude of risk reduction attenuated with increasing age. Conclusion: Metformin treatment is associated with a significantly reduced risk of diverticula of intestine.